1989
DOI: 10.1002/aja.1001840403
|View full text |Cite
|
Sign up to set email alerts
|

Renal anatomy of the manatee, Trichechus manatus, linnaeus

Abstract: The manatee kidney is composed of several closely apposed lobes. These are formed by cortical folds (plicae corticales) that completely isolate the medullae, except where the medullae of adjacent lobes are partially fused. The cortex is continuous; its folds usually are separated, but only partially, by interlobar septa extending from the renal capsule. The cortex makes up approximately 57% of renal mass in adults and 68% in the calf. There are about 3 million glomeruli per kidney. The average is somewhat less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
(27 reference statements)
0
23
0
Order By: Relevance
“…Glomeruli were counted as previously described (Maluf, 1989a(Maluf, , 1991a(Maluf, ,b, 1993. Briefly, a few grams of the central cortex of the previously frozen, thawed, and formaldehyde-fixed kidney were thoroughly mopped with absorbent paper and weighed to the nearest 0.1 mg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glomeruli were counted as previously described (Maluf, 1989a(Maluf, , 1991a(Maluf, ,b, 1993. Briefly, a few grams of the central cortex of the previously frozen, thawed, and formaldehyde-fixed kidney were thoroughly mopped with absorbent paper and weighed to the nearest 0.1 mg.…”
Section: Methodsmentioning
confidence: 99%
“…The present author, however, cannot corroborate Sperber's 9/10 ratio for cortexlkidney in Elephas. Furthermore, in the adult manatee, the cortex of which is rich in medullary loops, the cortical fraction of the renal parenchyma is relatively low (Maluf, 1989a). It is not clear how Sperber obtained the above ratio, since he noted that "the weight of the kidneys is not known either in my own alcohol kidneys or in most data from the literature.…”
Section: Lnterlobar Septamentioning
confidence: 95%
“…Although little is known about the maintenance of water in manatees, Maluf (1989) analyzing the anatomy of nine manatee kidneys (Trichechus manatus), suggested that they have an increased ability to concentrate urine. Since Trichechus manatus inhabits both freshwater and marine, it can be considered an interesting model for osmoregulation study in Sirenians.…”
Section: Specific Gravitymentioning
confidence: 99%
“…This is a relatively large fraction. In the writer's experience this fraction is outstripped by the adult manatees (Maluf, 1989a). In the two other adult Diceros bicornis females the medulla averaged 34.9% of the parenchymal mass (Maluf, 1991a).…”
Section: Medullamentioning
confidence: 94%
“…Counting of glomeruli has been described in detail (Maluf, 1989a(Maluf, , 1991a. Pieces of central cortex, checked by dissecting microscope to exclude possible residual medulla, were carefully mopped on absorbent paper and weighed to the nearest mg and then disintegrated at room temperature with 7.4 N (27%) HC1.…”
Section: Wiley-liss Incmentioning
confidence: 99%